PRICE STRATEGY AND SERVICE QUALITY AFFECTING REPURCHASE - Anggie Irwansyah; Rita Komaladewi; R. Thomas Budhyawan Yudha (Management Department, Faculty of Economics and Business, Universitas Jambi, 2022)
Regarding to health case in Indonesia, there is a shifting in people’s behaviour. They become more aware of their physical health, which is related to facial beauty and physical neatness, because physical neatness strongly reflects someone’s condition. People make habit visiting beauty clinics regularly to purchase various beauty services to stay beautiful. This beauty industry is commonly identical with women, but men slowly making the same habits as well, they begin to visit those beauty clinics almost everymonth. Usually they visit the clinics together with their wives or friends. These beauty customers mostly come from teenagers in schools or known as generation Z, to productive age people who works in various companies. As generation who live in digital era, generation Z have unique ways of thinking in comparison to the earlier generations, including in the world of beauty. In their annual report, ZAP Beauty Index shows that generation Z spends most of their money on beauty treatments, even 67.8% women from generation Z confess that they have body shamming experience triggered by ance problems, and their favourite beauty treatment is the treatment that utilizes laser. Because of this, beauty industry in the form of beauty clinics can blossom. As the results, competition among beauty clinics is inevitable, this research is about how price strategy and service quality formulated by an underdog beauty clinic in its efforts to maintain repurchase by the customers. The research is conducted in Tasikmalaya as a not famous city but having so much potentials for future.